Light through the fog: using precision fMRI data to disentangle the neural substrates of cognitive control. (August 2021) - Smith, Derek M; Perez, Diana C; Porter, Alexis; Dworetsky, Ally; Gratton, Caterina
Highlights: Cognitive control areas show high cross-subject variation in functional organization. Cross-subject variability can confound reports of control area multifunctionality. Precision fMRI can identify individualized functional regions linked to control. This approach may help disambiguate functional accounts of regions such as the dACC. We review the use of individualized methods to elucidate the neurobiology of control. Abstract : Cognitive control, the ability to engage in goal-related behavior, is linked to frontal, parietal, and cingulate brain regions. However, the underlying function(s) of these regions is still in question, with ongoing discussions about their specificity and/or multifunctionality. These brain regions are also among the most variable across individuals, which may confound multi-functionality with inter-individual heterogeneity. Precision fMRI—extended data acquisition from single individuals—allows for reliable individualized mapping of brain organization. We review examples of recent studies that use precision fMRI to surmount inter-individual variability in functional neuroanatomy. These studies provide evidence of interleaved specialized and multifunctional regions in the frontal cortex. We discuss the potential for these techniques to address outstanding controversies on the neural underpinnings of cognitive control.